THE ASSOCIATION BETWEEN ASTIGMATIC ANISOMETROPIA WITH VISUAL ACUITY AND STEREOPSIS - MOHAMAD BASIR, NUR HANANI; RUSLIM, NURUL HASMIZA; SOPIAN, SYUHAIRAH NABILAH; IBRAHIM, NURA SYAHIERA; AHMAD, NORSHAM; YUSOF @ ALIAS, FIRDAUS; MD MUSTAFA, MD MUZIMAN SYAH (International Journal of Allied Health Sciences, 2020)
Aim: To study the association between astigmatic anisometropia with visual acuity (VA) and stereopsis. Methodology: Twenty emmetropic adults with normal binocularity in age of 18 to 34 years old, were recruited. Unilateral against-the-rule astigmatism anisometropia was induced in each participant by using -1DC, -2DC, -3DC and -4DC toric soft contact lenses. Distance VA is measured using logMAR chart, near VA is measured using Roman Test types chart, and stereopsis using TNO plates were assessed. Results: All participants showed a reduction in VA at distance and near, and stereopsis with the increasing values of astigmatic anisometropia by using correlation analysis. The correlation of induced astigmatic anisometropia with distance VA was a weak positive correlation, (r = 0.589, p = <0.05), and moderate positive correlation (r = 0.602, p = <0.05) with near VA. Stereopsis was similarly degraded and showed weak positive correlation (r = 0.589, p = <0.05). Both acuities showed significant reduction in each 1D increment of astigmatic anisometropia by 1 line, meanwhile stereopsis showed significant reduction by 2 lines. Stereopsis is affected the most. All parameters reduction can be predicted by using linear regression equation obtained, at any degree of astigmatic anisometropia. Conclusion: Increment in induced astigmatic anisometropia shown linear reduction in distance VA, near VA and stereopsis.